Semi-public watermarking digital implementation in the concealment of text messages - Sitompul, Noferianto; Maranata Pasaribu (SEAN Institute, 2021)
The purpose of this study is to generate watermarking of an input image. The watermarking process will begin with the process of reading color image pixels. After that, the process will be continued by calculating the step message value inserted and inserting all the necessary values in the watermarking checking process. In the event of an attack, then at the time of watermarking formation, a specific noise value (randomly generated) will be calculated to be inserted into the image. After the process of watermarking formation, then the process can be continued with checking watermarking and extracting messages.